The relationship between teacher care behavior and EFL learning anxiety: the chain mediation effect of learning engagement and learning strategies - Wang, Dongmei (Frontiers in Psychology, 2023)
This study aims to discuss the impact of teacher care behavior on EFL learning anxiety, as well as the mediating role of learning engagement and learning strategies. The Process plugin Model6 was used to measure the interaction between teacher care behavior (TCB), EFL learning anxiety (EFLLA), learning engagement (LE), and English learning strategies (ELS), in order to analyze and summarize their impact characteristics on college students’ EFL learning anxiety. The results show that teacher care behavior has a direct impact on EFL learning anxiety and a significant negative predictive effect on it. Learning engagement and English learning strategies play a mediating and chain mediating role between teacher care behavior and EFL learning anxiety. Thus, it can be seen that these factors can help reduce EFL learning anxiety, manifested in aspects such as mood, cognition, emotion, and behavior. Given the research findings, this study further provides suggestions for alleviating college students’ EFL learning anxiety, optimizing English teaching and learning design, and cultivating English learning strategies for college students.